A preliminary investigation into the use of the invasive golden apple snail, Pomacea canaliculata (Lamarck, 1822), as a water purifier and food source in the breeding ponds of the oriental weatherloach Misgurnus anguillicaudatus (Cantor, 1842). (3rd July 2018) - Guo, Jing; Xiang, Yao; Zhang, Chunxia; Zhang, Jia-en
ABSTRACT: This study investigated the feasibility of using an invasive snail, Pomacea canaliculata, as a food source and water purifier for the commercial breeding of the loach Misgurnus anguillicaudatus . The predatory potential of M. anguillicaudatus (3.5–5.5 g) against hatchling snails was evaluated in aquaria and simulated paddy fields. Some hatchling snails left the water to avoid being preyed upon by the loaches, and approximately 10 hatchlings died per day in the presence of five loaches in aquaria, whereas a weaker snail control effect was observed in the simulated paddy fields. The growth of rice seedlings ( Oryza sativa ) was not reduced by the presence of hatchling snails alone, but the shoot biomass of seedlings coexisting with snails was promoted after introducing the loaches. Additionally, the presence of P. canaliculata adults improved the aquatic environment in the short term for loach breeding by decreasing the turbidity of the water. Importantly, M. anguillicaudatus (12–18 g) mortality decreased and its weight increased in the presence of adult snails.